The Strategic Value of China's Foreign Policy and The Rivalry of The Majors Power in The Indo-Pacific - Alunaza, Hardi; Sherin, Virginia (Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The Indo-Pacific in the development of world politics is a meeting place for stakeholders from the US, China, Japan, India, Australia, and ASEAN to articulate each country's strategic interests. The rivalry between the US and China has been referred to as the new cold war in Southeast Asia. This momentum is an excellent opportunity for ASEAN to develop and expand its role in the Indo-Pacific by emphasizing centrality and putting its role to good use. Including the challenges of how China projects its strategic values to Australia, Japan, and India. This research analyzes the strategic value and emerging challenges of Majors Power in the Indo-Pacific. This article uses the theory balance of power with a qualitative descriptive method. It explains how China expands its influence in the Indo-Pacific region by increasing the distribution of rising power, new security concepts, peaceful rise, engagement, and comprehensive establishments and how this strategic value poses a challenge to India, the US, Australia, and Japan. The rise of the Indo-Pacific is one of the influences involving the superpowers by looking at the potential in the region. This is inextricably linked to China's national interest. The results of this research is that China uses the strategic value of rising power and new security concepts in its rivalry with the US and ASEAN. Concerning Australia, China prioritizes engagement and comprehensive establishment by leveraging economic benefits. In addition, China has shown a peaceful rise and engagement, as well as geopolitical rivalries with Japan and India.